COVID-19: From evaluating impact to reimagining strategy and policy - Breisinger, Clemens (2020)
“IFPRI Egypt Webinars” is a special edition of the IFPRI Egypt Seminar Series funded by USAID. This webinar took place in partnership with the Egyptian Center for Economic Studies (ECES), under the title of "COVID-19 and the Egyptian Economy: Modeling Impacts and Next Policy Steps"